Manuel Correia de Andrade: in small texts, the world - Buitoni, Dulcilia Helena Schroeder (Revista do Instituto de Estudos Brasileiros, 2023)
The Documentation section makes room for original texts by geographer Manuel Correia de Andrade and for images of books from his library. These are documents that are part of the immense collection donated to the Institute of Brazilian Studies, a collection that is in the process of being cleaned and catalogued. Excerpts were selected that show how this intellectual articulated research, culture and political and social context. Topics such as development, poverty, environmental issues, corruption and decolonial thinking appear – pioneering, as this concept had not yet been introduced into Brazilian academic circles.